Associations between precipitation, temperature, and malaria prevalence in children under 5 in Mali - Niklas J.T. Hayden; Joey Syer; Stephanie K. Yanow; Shelby S. Yamamoto (PLoS ONE, 2026)
Malaria is prevalent in Mali and children under 5 are more vulnerable. Temperature and precipitation can affect vector density and parasite development, impacting malaria transmission. This exploratory study aimed to investigate potential associations between changes in precipitation and temperature and prevalence of malaria infection in children under 5 in Mali. A cross-sectional study was conducted using data from the Mali Demographic and Health Surveys and Malaria Indicators Surveys conducted in 2012/13, 2015, 2018, and 2021. We examined malaria prevalence diagnosed by rapid diagnostic tests (RDT) in children ages 6–59 months. Exposures included precipitation and temperature (minimum, maximum, average). Three monthly lags were created for each exposure. Multilevel modelling was conducted to assess the relationships between exposures and malaria for each lag in a pooled analysis of the survey years. With a three month lag, precipitation was statistically significantly positively associated with the odds of RDT-diagnosed malaria in children ages 6–59 months (Odds ratio (OR) [95% CI], 1.005 [1.002, 1.009]) and minimum, maximum, and average temperature were statistically significantly negatively associated with the odds of malaria (Minimum temperature = 0.761 [0.621, 0.931], maximum temperature = 0.871 [0.791, 0.958], average temperature = 0.822 [0.718, 0.942]). With a two month lag, maximum temperature was statistically significantly negatively associated with the odds of malaria (0.863 [0.750, 0.992]). At a one month lag, minimum temperature was statistically significantly positively associated with the odds of malaria (1.110 [1.014, 1.216]). All other results were not statistically significant. Precipitation may be a risk factor for malaria infection in children under 5 in Mali. Temperature alone is likely not contributing to changes in the odds of malaria infection, particularly when considering precipitation. Future studies focusing on regional-specific differences are needed to fully understand the relationships.